2020
DOI: 10.1002/ams2.609
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcome of patients triaged by telephone and transported by ambulance: a population‐based study in Osaka, Japan

Abstract: Aim: Details such as diagnosis and outcome of patients transported by ambulance after telephone triage have not been fully revealed. The aim of this study was to reveal profile and outcome about patients transported by ambulance via telephone triage with dataset of telephone triage and population-based registry for emergency patients. Methods: This retrospective descriptive study with a one-year study period from January 1, 2016 to December 31, 2016 included patients selected from the telephone triage dataset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…We already showed that 33% of cases, who were assigned to category red by Step 3 (symptom-speci c protocols) in the #7119 telephone triage were moderate, severe, lethal, and dead, as in cases with severity according to the de nition of this study [22]. Katayama et al reported that 29.2% of patients transported by ambulance after telephone triage were hospitalized [23]. We share almost the same protocol of telephone triage and prehospital emergency ambulance system as their study in Japan.…”
Section: Discussionmentioning
confidence: 49%
“…We already showed that 33% of cases, who were assigned to category red by Step 3 (symptom-speci c protocols) in the #7119 telephone triage were moderate, severe, lethal, and dead, as in cases with severity according to the de nition of this study [22]. Katayama et al reported that 29.2% of patients transported by ambulance after telephone triage were hospitalized [23]. We share almost the same protocol of telephone triage and prehospital emergency ambulance system as their study in Japan.…”
Section: Discussionmentioning
confidence: 49%
“…We previously described the profile of patients who were transported by ambulance after telephone triage in Osaka Prefecture [ 5 ]. The most common time of day for both telephone triage and use of this app was in the evening.…”
Section: Discussionmentioning
confidence: 99%
“…The telephone triage service in Osaka Prefecture has been described previously in detail [ 5 , 11 ]. The telephone triage nurses who receive phone calls from people judge the urgency of the chief complaints using software based on the Emergency Assessment Protocol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations